Amide activation: an emerging tool for chemoselective synthesis. (28th August 2018) - Kaiser, Daniel; Bauer, Adriano; Lemmerer, Miran; Maulide, Nuno
Abstract : This review focusses on the use of amide activation for chemoselective functionalisation and its application in natural product synthesis. Abstract : It is textbook knowledge that carboxamides benefit from increased stabilisation of the electrophilic carbonyl carbon when compared to other carbonyl and carboxyl derivatives. This results in a considerably reduced reactivity towards nucleophiles. Accordingly, a perception has been developed of amides as significantly less useful functional handles than their ester and acid chloride counterparts. However, a significant body of research on the selective activation of amides to achieve powerful transformations under mild conditions has emerged over the past decades. This review article aims at placing electrophilic amide activation in both a historical context and in that of natural product synthesis, highlighting the synthetic applications and the potential of this approach.